2017
DOI: 10.1007/s00425-017-2748-y
|View full text |Cite
|
Sign up to set email alerts
|

Floral nectary, nectar production dynamics and chemical composition in five nocturnal Oenothera species (Onagraceae) in relation to floral visitors

Abstract: Main conclusion The floral nectars were sucrose-dominant; however, nectar protein and amino acid contents differed, indicating that composition of nitrogenous compounds may vary considerably even between closely related plant species, irrespectively of nectary structure. Numerous zoophilous plants attract their pollinators by offering floral nectar; an aqueous solution produced by specialized secretory tissues, known as floral nectaries. Although many papers on nectaries and nectar already exist, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Our findings are consistent with those of the latter authors and demonstrate that, apart from prior selfing, visits by bees may lead to effective transfer of outcross pollen in the investigated species of Oenothera. Furthermore, in another, complementary project (Antoń et al 2017), we reported that the complex pattern of nectar production and nectar distribution along the inflorescences of these taxa may determine the movement of pollinators between individual plants, thereby promoting cross-pollination. These observations all indicate that the breeding system present in subsect.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our findings are consistent with those of the latter authors and demonstrate that, apart from prior selfing, visits by bees may lead to effective transfer of outcross pollen in the investigated species of Oenothera. Furthermore, in another, complementary project (Antoń et al 2017), we reported that the complex pattern of nectar production and nectar distribution along the inflorescences of these taxa may determine the movement of pollinators between individual plants, thereby promoting cross-pollination. These observations all indicate that the breeding system present in subsect.…”
Section: Discussionmentioning
confidence: 92%
“…It is generally agreed that the great requirement of pollinators for energy necessitates the uptake of much nectar (Nicolson 2007 and references therein). In the case of the species of Oenothera studied, insect visitors were attracted to the flower by both copious amounts of floral nectar (i.e., up to 26.8 mg/flower; Antoń et al 2017) and pollen (i.e., up to 6.4 mg/flower; Antoń and Denisow 2018) that were constantly accessible from the onset of anthesis (i.e., evening hours) until the start of flower senescence (i.e., early morning hours). It is also worth noting that it has been proposed for other species of subsect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations